Comunicação digital de moda: entre o visível e o volátil na construção de imagens de marca - Hallage, Mariana Leonhardt (2018)
This study intends to understand how fashion brands keep their strategies of branding and its own stories, while being internet’s social agents, through real time communication in digital social medias. The analysis is based by the view of the conflicting dynamic between the need showed by brands to be always visible and the scheduled volatility of images and videos produced in the cyberspace, particularly in social medias which its premise surrounds the idea of producing content units that lasts in visibility only for only day after being created and started its disclosure. To achieve this main reflection of thoughts, we intend to analyze the ephemeral audiovisual content production that three brands, being in the market as fast-fashions, besides of observing how they hand with their own image complexities by passing information of branding for volatile images. The logic of digital communication in real time and the one of fashion system are incredibly like each other, in terms of language and expressions of the needs of these brands, which will be also included here, in conclusion of this study. It will be elaborated case studies analyzing the brands C&A Brasil, Forever21 and Topshop, in their activities on digital social medias Snapchat and Instagram Stories, by collecting sixty days of image production. Talking about results, we could found content units which helps on the creation of a singular narrative strategy for each brand, maintaining their media visibility to their spectators